At the crossroads : African Caribbean religion & Christianity - Sankeralli, Burton ed. (Caribbean Conference of Churches St. JamesTT, 1995)
Presents a collection of papers which were presented at an ecumenical conference on popular religiosity in Lelydorp, Suriname in May 1994. Highlights some of the thinking that is taking place in the region about Christianity and its relationship with other religions.